KONTRIBUSI KEADILAN ORGANISASI DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA PEGAWAI - Muh. Ryamizard Rasyid; Herman Sjahruddin; Muhammad Umar Data (LP2M Universitas Bina Bangsa, 2024)
Preliminary observations suggest that judicial practices among government bureaucracy workers are not optimally implemented. There are also some employees who do not feel as fair as their colleagues, which affects their performance that is not yet optimal, and also affects their personal characteristics that are far from being achieved. Consistency with the tasks and work assigned to them, thus affecting their work results both qualitatively and quantitatively, resulting in their poor performance. The purpose of this study is to determine the impact of organizational justice and personal characteristics on employee performance in Panakukang Makassar Regional Office. The type of research adopted in this study was quantitative research with 55 employees as respondents and population sampling technique was used as the puposive sampling technique. Data analysis using multiple linear regression with the SPSS 27.0 program provides evidence that organizational justice has a positive and significant effect on employee performance. Regarding the contribution of other variables, it was found that individual characteristics contributed positively but not significantly to employee performance